2010
DOI: 10.1155/2010/474692
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Circulating miR-221 for Extranodal Natural Killer/T-Cell Lymphoma

Abstract: Extra-nodal natural killer T-Cell (NK/T-cell) lymphoma is a progressive cancer with poor prognosis due to the lack of disease specific treatment. To develop specific therapeutic strategies, it is essential to identify tumor markers. Recent studies show that circulating microRNA (miRNA) may serve as diagnostic and/or prognostic markers for some diseases. To explore miRNAs as potential diagnostic and/or prognostic markers of NK/T-cell lymphoma, in our study, we compared circulating miR-221 levels in 79 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…Lawrie and colleagues found that serum levels of miR-155, miR-210, and miR-21 were higher in patients with diffuse large B-cell lymphoma (DLBCL) than control sera, and high expression was associated with reduced relapsefree survival (8). Elevated serum levels of miR-155 in DLBCL were validated in a subsequent study (13) and circulating miR-221 was raised pretherapy in extra nodal natural killer/T-cell Lymphoma (14). However, in these three studies, no sequential samples were taken to investigate whether serial monitoring may have clinical utility as disease response biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Lawrie and colleagues found that serum levels of miR-155, miR-210, and miR-21 were higher in patients with diffuse large B-cell lymphoma (DLBCL) than control sera, and high expression was associated with reduced relapsefree survival (8). Elevated serum levels of miR-155 in DLBCL were validated in a subsequent study (13) and circulating miR-221 was raised pretherapy in extra nodal natural killer/T-cell Lymphoma (14). However, in these three studies, no sequential samples were taken to investigate whether serial monitoring may have clinical utility as disease response biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, circulating levels of miR-141 along with 15 other microRNAs (miR-16, miR-92a, miR-92b, miR-103, miR-107, miR-197, miR-34b, miR-328, miR-485-3p, miR-486-5p, miR-574-3p, miR-636, miR-640, miR-766, and miR-885-5p) have been found to be higher in patients than in healthy controls [21,26]. In addition, circulating miR-221 has been shown to be higher in patients with ovarian cancer, melanoma, and lymphoma compared to healthy controls [27,28,29]. Taken together these studies suggest that microRNA biomarkers may be more sensitive than current circulating protein biomarkers, and than imaging techniques in cancer diagnosis (Table 1).…”
Section: Micrornas As Biomarkersmentioning
confidence: 99%
“…109 Plasma miR-221 has been found to be a good diagnostic and prognostic marker for extranodal natural killer T-cell lymphoma. 110 Clearly, although the results are very preliminary, the ability of miRNAs to act as noninvasive biomarkers of BCLs is a promising prospect.…”
Section: Mirnas As Noninvasive Biomarkers Of B-cell Lymphomamentioning
confidence: 99%